Inositol polyphosphate–protein interactions: Implications for microbial pathogenicity. (25th March 2021) - Lev, Sophie; Bowring, Bethany; Desmarini, Desmarini; Djordjevic, Julianne Teresa
Abstract: Inositol polyphosphates (IPs) and inositol pyrophosphates (PP–IPs) regulate diverse cellular processes in eukaryotic cells. IPs and PP–IPs are highly negatively charged and exert their biological effects by interacting with specific protein targets. Studies performed predominantly in mammalian cells and model yeasts have shown that IPs and PP–IPs modulate target function through allosteric regulation, by promoting intra‐ and intermolecular stabilization and, in the case of PP–IPs, by donating a phosphate from their pyrophosphate (PP) group to the target protein. Technological advances in genetics have extended studies of IP function to microbial pathogens and demonstrated that disrupting PP–IP biosynthesis and PP–IP‐protein interaction has a profound impact on pathogenicity. This review summarises the complexity of IP‐mediated regulation in eukaryotes, including microbial pathogens. It also highlights examples of poor conservation of IP–protein interaction outcome despite the presence of conserved IP‐binding domains in eukaryotic proteomes.